Social Disorganisation and Feeling Safe: Insights from Diverse Scottish Neighbourhoods - Moh. Dede; Millary Agung Widiawaty; Elly Malihah; Sunardi Sunardi; Puspita Wulandari; Heni Susiati; Dina Oktavia (JAMBURA GEO EDUCATION JOURNAL, 2025)
Neighbourhood safety remains a critical urban challenge, with social disorganisation theory positing that structural factors like poverty and residential instability weaken community cohesion and amplify crime perceptions. While Scotland has seen declining crime rates, persistent violence in deprived areas, and emerging disorder in affluent communities necessitate safety measures across socioeconomic situations. This study examines how social disorganisation influences perceptions of safety across affluent and deprived neighbourhoods in Edinburgh and Glasgow, Scotland. Using a cross-sectional survey of 610 residents, we employed multiple regression and ANOVA models to analyse six key indicators of social disorder (noise, vandalism, verbal abuse, burglary, unsupervised children, and physical assault) against self-reported feelings of safety. Data were transformed using the Item Response Theory and Rasch Model to enable parametric analysis, with cross-validation confirming model robustness (R² 0.92).  Results revealed that verbal abuse (β = -0.565) and physical assault (β = -0.499) were the strongest predictors of reduced safety, with deprived areas exhibiting heightened vulnerability. Counterintuitively, affluent neighbourhoods reported higher perceived disorder for vandalism and unsupervised children, suggesting socioeconomic differences in reporting behaviours or tolerance thresholds. City-specific variations emerged: vandalism significantly impacted safety in Glasgow’s deprived areas but not Edinburgh’s, highlighting the need for locally tailored interventions.  The findings reinforce social disorganisation theory while demonstrating its nuanced application across socioeconomic contexts. Urban safety research by incorporating minor incivilities often overlooked in crime statistics, offering evidence for holistic approaches to neighbourhood security.